2018
DOI: 10.1016/s0140-6736(17)32471-6
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular, respiratory, and related disorders: key messages from Disease Control Priorities, 3rd edition

Abstract: Cardiovascular, respiratory, and related disorders (CVRDs) are the leading causes of adult death worldwide, and substantial inequalities in care of patients with CVRDs exist between countries of high income and countries of low and middle income. Based on current trends, the UN Sustainable Development Goal to reduce premature mortality due to CVRDs by a third by 2030 will be challenging for many countries of low and middle income. We did systematic literature reviews of effectiveness and cost-effectiveness to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
79
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(85 citation statements)
references
References 76 publications
(78 reference statements)
1
79
0
5
Order By: Relevance
“…hile cardiovascular diseases (CVDs) threaten human health with the lifetime risk exceeding 30%, myocardial infarction (MI) is the leading cause of death for CVDs nowadays 1,2 . Notably, the influence of MI is becoming more severe in recent decades with an annual growth rate of over 3.6% 3,4 , due to changes in human behavior and lifestyle, particularly in developing countries 5,6 . Considering the substantial progress in the treatment of MI, current management of MI is focused on diagnostic and prognostic approaches, which can reduce the medical costs and raise the survival ratio as well as life quality of patients 7,8 .…”
mentioning
confidence: 99%
“…hile cardiovascular diseases (CVDs) threaten human health with the lifetime risk exceeding 30%, myocardial infarction (MI) is the leading cause of death for CVDs nowadays 1,2 . Notably, the influence of MI is becoming more severe in recent decades with an annual growth rate of over 3.6% 3,4 , due to changes in human behavior and lifestyle, particularly in developing countries 5,6 . Considering the substantial progress in the treatment of MI, current management of MI is focused on diagnostic and prognostic approaches, which can reduce the medical costs and raise the survival ratio as well as life quality of patients 7,8 .…”
mentioning
confidence: 99%
“…For implementation of the END TB strategy, it is recommended that "All persons with TB need to be assessed for nutritional status and receive nutritional counselling and care according to need" and additionally, "all persons with TB should be screened for diabetes" and, "in addition to HIV/AIDS, other co-morbidities and health risks associated with TB require integrated management" 9 . Both diabetes and TB can increase the short and long-term risk of cardiovascular 10 and respiratory conditions 11 requiring lifelong management to reduce population health and economic impacts and are recognised as priorities for cost-effective disease control 12,13 . As well as increasing the risk of developing active TB disease, untreated participants.…”
mentioning
confidence: 99%
“…The second example of contextualisation influencing implementation of NCD prevention and control comes from studies of fixed-dose combinations or polypill therapy. Polypills represent a strategy to implement costeffective, multi-drug regimens for patients with or at high predicted risk for cardiovascular diseases [9]. In 2019, the PolyIran trial demonstrated that the combination of aspirin, atorvastatin, and either lisinopril or valsartan led to a 34% lower risk (95% CI 20-45%) for cardiovascular events compared with usual care over 5 years when implemented in a large, cluster-randomized trial across 236 villages (n = 6,838 participants) in Iran [10].…”
Section: Fixed-dose Combination Therapy For Cardiovascular Disease Prmentioning
confidence: 99%